Fixed Rehabilitation of an ACP PDI Class IV Dentate Patient - Yasuhiro Tanimoto, PhD1 and Kimiya Nemoto, DDS, PhD2 (Journal of Prosthodontics, 2006)
The purpose of this study was to investigate the effect of sintering temperature on flexural properties of an alumina fiber-reinforced, alumina-based ceramic (alumina-fiber/alumina composite) prepared by a tape casting technique.